2000
DOI: 10.1054/bjoc.2000.1199
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cells in bone marrow of oesophageal cancer patients: a significant prognostic factor in multivariate analysis

Abstract: The detection of epithelial cells in bone marrow, blood or lymph nodes indicates a disseminatory potential of solid tumours. 225 patients with squamous cell carcinoma of the oesophagus were prospectively studied. Prior to any therapy, cytokeratin-positive (CK) cells in bone marrow were immunocytochemically detected in 75 patients with the monoclonal anti-epithelial-cell antibody A45-B/B3 and correlated with established histopathologic and patient-specific prognosis factors. The prognosis factors were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 26 publications
(29 reference statements)
3
31
1
1
Order By: Relevance
“…The authors concluded that an autocrine CXCL12 secretion from tumor cells might activate CXCR4 on the tumor cells, resulting in distant metastases. The interaction of gastric cancer-expressed CXCR4 and SDF-1α may be a key event in directing malignant cells to homing organs, which is underlined by findings in esophageal cancer, where the presence of micrometastatic tumor cells in lymph nodes and bone marrow was associated with poorer survival (22,23). As demonstrated in pancreatic cancer, CXCL12 is secreted by cancerous lesions and flows via lymphatic or venous routes to its metastatic sites (24).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that an autocrine CXCL12 secretion from tumor cells might activate CXCR4 on the tumor cells, resulting in distant metastases. The interaction of gastric cancer-expressed CXCR4 and SDF-1α may be a key event in directing malignant cells to homing organs, which is underlined by findings in esophageal cancer, where the presence of micrometastatic tumor cells in lymph nodes and bone marrow was associated with poorer survival (22,23). As demonstrated in pancreatic cancer, CXCL12 is secreted by cancerous lesions and flows via lymphatic or venous routes to its metastatic sites (24).…”
Section: Discussionmentioning
confidence: 99%
“…At diagnosis, 80% of cases are inoperable (2) and, of those with early local disease who have surgery as part of their treatment, only 15% to 30% will be cured (3 -5).…”
mentioning
confidence: 99%
“…As taxas de detecção de micrometástase variam de 15 a 38,7%, na medula óssea da crista ilíaca. Thorban et al 28 , em análise multivariada, mostrou importância prognóstica significativa na detecção de micrometástase de medula óssea em pacientes com carcinoma espinocelular de esôfago. Foi evidenciado mau prognóstico de pacientes citoqueratina-positiva em comparação a citoqueratina-negativos com diminuição significativa no tempo de sobrevida geral.…”
Section: Micrometástasesunclassified